2017
DOI: 10.1016/j.ijppaw.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of the mosquito-borne filarial nematode Setaria tundra in Danish roe deer ( Capreolus capreolus )

Abstract: Setaria tundra is a mosquito-borne filarial nematode of cervids in Europe. It has recently been associated with an emerging epidemic disease causing severe morbidity and mortality in reindeer and moose in Finland. Here, we present the first report of S. tundra in six roe deer (Capreolus capreolus) collected between October 2010 and March 2014 in Denmark. The deer originated from various localities across the country: the eastern part of the Jutland peninsular and four locations on the island Zealand. With the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…vexans on C. capreolus revealed in the study performed in Germany (Börstler et al 2016) and identical S. tundra COI gene fragment sequences (Table 1) found in C. capreolus and Ae. vexans from Poland (in this study and in the study by Masny et al 2016), Germany (Kronefeld et al 2014), Denmark (Enemark et al 2017), Hungary (Zittra et al 2015), France (Ferri et al 2009), Italy (Favia et al 2003), and Spain (Angelone-Alasaad et al 2016) are an indication that Ae. vexans acquires S. tundra by feeding on C. capreolus .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…vexans on C. capreolus revealed in the study performed in Germany (Börstler et al 2016) and identical S. tundra COI gene fragment sequences (Table 1) found in C. capreolus and Ae. vexans from Poland (in this study and in the study by Masny et al 2016), Germany (Kronefeld et al 2014), Denmark (Enemark et al 2017), Hungary (Zittra et al 2015), France (Ferri et al 2009), Italy (Favia et al 2003), and Spain (Angelone-Alasaad et al 2016) are an indication that Ae. vexans acquires S. tundra by feeding on C. capreolus .…”
Section: Discussionsupporting
confidence: 55%
“…infections. The parasite S. tundra was documented in many European countries: in reindeer in the former USSR (Rajewsky 1928), in reindeer from Sweden (Rehbinder 1990) and Norway (Kummeneje 1980), in roe deer from Bulgaria (Yanchev 1973) and Germany (Büttner 1978; Rehbein et al 2000; Czajka et al 2012), and roe deer from Italy (Favia et al 2003), Poland (Bednarski et al 2010; Kowal et al 2013; Kuligowska et al 2015), and Denmark (Enemark et al 2017). The veterinary importance of S .…”
Section: Introductionmentioning
confidence: 99%
“…Wolbachia has also previously been isolated from W. bancrofti , Brugia malayi , O. volvulus , and Setaria tundra (29, 4042). Recently, the study of the isolated O. volvulus from 4 African countries indicated that extensive intra species heterogeneity exists in the Wolbachia content of male and female adults of O. volvulus .…”
Section: Discussionmentioning
confidence: 99%
“…as vectors (vector-borne disease). Czajka et al (2012) screened mosquitoes in Germany for filarial parasites using RT PCR, and found minimum prevalence rates of up to 24 infected per 1000 mosquitoes, which were attributed mainly to Setaria tundra infection. In the final hosts adult females that inhabit the peritoneal cavity produce large numbers of microfilariae each day (in thousands) which end up in the blood (Nelson, 1966), and are taken up by the vectors.…”
Section: Introductionmentioning
confidence: 99%